Sosialisasi Sanitasi dan Air Bersih Terhadap Pencegahan Stunting di Posyandu Seroja Kota Samarinda - Suwignyo; Rindha Mareta Kusumawati; Kartina Wulandari; Apriyani (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Short toddlers (stunting) can be detected when a toddler has been measured in length or height, then compared with the standard, and the results are below normal. Short toddlers are toddlers with nutritional status based on length or height according to age when compared to the 2005 WHO-MGRS (Multicentre Growth Reference Study) standard, the z-score value is less than -2SD and is categorized as very short if the z-score is less from -3SD. Based on data on the stunting prevalence of East Kalimantan province in 2018-2020, especially in Samarinda in 2018, stunting cases were 26.26% in 2019 decreased by 24.75 and in 2020 remained at 24.7%. Meanwhile, based on data from the Samarinda City Health Office, in 2020 the prevalence of stunting was 11.9% and in 2021 it decreased by 10.7%. This service was carried out in July 2022 at one of the Posyandu in Kota Samarinda, namely at the Seroja Posyandu, Java Village, Samarinda Ulu District, Samarinda City. The service method used in this activity is the socialization of stunting prevention efforts. The main targets of this activity are pregnant women and toddlers who have been registered at the Seroja Posyandu. This activity began with socialization about sanitation and clean water on stunting and continued with a question and answer session. All activities that have been carried out went well.